Penggunaan Media Powerpoint Dalam Pembelajaran Musik Tradisional Di SMP Negeri 1 Bukittinggi - Yolla Paramita; Yensharti Yensharti (FBS Universitas Negeri Padang, 2021)
This research was conducted at SMP Negeri 1 Bukittinggi. The purpose of this study is to see the improvement of student learning outcomes taught by using Powerpoint Media in Teaching Traditional Music at SMP Negeri 1 Bukittinggi. This research belongs to a Classroom Action Research. It is intended to solve problems in the classroom to improve student learning outcomes. The research used the Kemmis and Taggart model which consists of 2 cycles having 4 stages: planning, implementing, observing, and reflecting. The data were collected quantitatively to see learning outcomes, and were collected qualitatively to provide an overview of students' abilities in learning. Other data were collected through observation, learning achievement tests, and documentation. The research was conducted in 2 meetings consisting of 2 cycles which were conducted face-to-face and online. Based on the results of the study, the average score got in cycle 1 is 73.03%, the score for classical absorption is 73.03%, and the score for mastery of learning is 21.87%. In the second cycle, the average value is 86.16%, classical absorption is 86.15%, and mastery learning is 84.37%. The percentage of student absorption in cycle II has increased by 13.12%. Based on this percentage, it can be seen that students have good success in the learning process using PowerPoint media in learning traditional music. Judging from the scores, students in grade VIII F have met the assessment standards which is 75. PowerPoint media can increase enthusiasm for student learning seen from the observation data and data analysis results in cycle I and cycle II. PowerPoint media can create innovative and creative learning so that learning objectives can be maximally achieved.